ANALISIS KONTRIBUSI SEKTOR PARIWISATA TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN GORONTALO - Kalzum R. Jumiyanti (International Interdisciplinary Conference on Sustainable Development Goals, 2018)
This research aims to know the contribution of employment in tourism, hotel and restaurants sectors particularly to the employment of Tourism industry sector in Gorontalo Recency. Type and data source use the qualitative approach with secondary data observed during 2010 TO 2017. Research data obtained through documenting in related institutions, processed by usingmethod of analysis of tourism sector contribution to the Employment. Research question is what is the percentage of Tourism sector contribution to the Employment in Gorontalo Recency. The research result shows that in 2010 the Employment of Tourism sector was 24.810 workforce or 15,86% of the total employment. In 2011 there was a decline around 1.68% or the contribution in percentage around 14.18%. In 2012, the Employment was 21.198 or 14,26 %. In 2013 there was an increase around 1.67 % or the contribution percentage around 15,93%. In 2014 there was a decline again around 1,21% or the contribution percentage around 14,72%. In 2015, there was a significant increase which was 4,02% or 18,72% of the contribution percentage or the number of employment in 2015 was 29.533 people. In 2016 the data was not provided because the Susenas (Social Economy Survey) was not conducted. In 2017, there was an increase in the percentage which was around 0,96% or the percentage contribution was 19,70%, it means the Employment in 2017 was 33.929 people. The contribution in tourism sector to the Employment during 2010 to 2017 in Gorontalo Recency can be stated as less than 20%.